Biopsy-detected myocardial fibrosis predicts adverse cardiac events after pulmonary valve replacement in patients with repaired tetralogy of Fallot. Issue 3 (3rd February 2023) - Yuan, Jianhui; Su, Zhanhao; Wang, Guanxi; Yang, Keming; Zhang, Benqing; Ma, Kai; Zhang, Sen; Yang, Yang; Feng, Zicong; Mao, Fengqun; He, Qiyu; Dou, Zheng; et al.
Abstract: OBJECTIVES: Risk factors associated with adverse cardiac events (cardiac AEs) after pulmonary valve replacement (PVR) in patients with repaired tetralogy of Fallot are incompletely understood. In this study, we aimed to determine the relationship between histological myocardial fibrosis and cardiac AEs after PVR in patients with rTOF. METHODS: We consecutively collected clinical, cardiac magnetic resonance, echocardiography and electrocardiogram data of 51 patients with rTOF who underwent surgical PVR. The right ventricular outflow tract tissue was collected during the PVR and the degree of histological myocardial fibrosis was determined by a tailor-made automated image analysis method of picrosirius red staining. RESULTS: The median follow-up time was 4.9 years, and 14 patients had cardiac AEs (a composite of heart failure admission and arrhythmia) during follow-up. The total analysis area of myocardial samples was 5782.18 mm 2, and the median percentage of myocardial fibrosis was 20.6% (interquartile range 16.7–27.0%), which were significantly elevated in patients with cardiac AEs compared with patients without cardiac AEs (24.1% vs 19.7%, P = 0.007). Right ventricular ejection fraction and left ventricular end-systolic volume index were significantly associated with myocardial fibrosis in multivariable stepwise linear regression analysis ( R 2 = 0.238). Cox proportional hazards regression identified degree of myocardial fibrosis [hazard ratio 1.127; 95% confidence interval (CI) 1.047–1.213; P = 0.001] and age at PVR (hazard ratio 1.062; 95% CI 1.010–1.116; P = 0.019) were associated with increased risk of cardiac AEs. The incidence of adverse cardiac events was significantly increased when myocardial fibrosis >20.1% and age at PVR >18.2 years. CONCLUSIONS: Histological myocardial fibrosis was associated with biventricular systolic functions in rTOF. Higher myocardial fibrosis and older age at PVR are independent risk factors for the adverse cardiac events after PVR in patients with rTOF. Abstract : Repair of tetralogy of Fallot in young children prolongs their survival but could be associated with heightened risk of postoperative pulmonary regurgitation (PR), which significantly increases volume overload in the right ventricle.